Promoting resilient and sustainable food systems: a systematic literature review on short food supply chains - Jia, Fu; Shahzadi, Gulnaz; Bourlakis, Michael; John, Albert (Elsevier, 2024)
Purpose This review aims to comprehensively analyze the Short Food Supply Chain (SFSC) model, which connects local food producers directly with consumers. By exploring participation factors, sustainable practices, challenges, economic impacts, and social benefits, this study seeks to provide a thorough understanding of SFSCs. Addressing gaps in existing research, the review aims to guide policymakers and practitioners in fostering sustainable, resilient, and inclusive local food systems. Design/methodology/approach A systematic literature review of 92 research articles was conducted following a well-defined research protocol. Findings The review revealed that factors driving the adoption of SFSCs include increasing consumer demand for local and sustainable products, resilience-building in the food system, and environmental concerns. The SFSC supply chain was categorized into four critical stages: food sourcing and production, processing, aggregation, and distribution and review examined the sustainable practices at each stage. However, challenges such as information asymmetry, lack of infrastructure, regulatory barriers, and market dynamics hinder the full potential of SFSCs. Economically, SFSCs contribute to local economic development and empowerment of small-scale producers, while also showing promise in reducing environmental footprints and fostering community engagement. Research implications The study identifies several research avenues to further advance the understanding of SFSCs. Future research should delve into consumer behavior and attitudes towards SFSCs, analyze the full sustainability impacts of SFSCs using integrated assessment methodologies, and extend the study to different regional contexts. Additionally, investigating policy interventions and governance mechanisms that can support the growth and resilience of SFSCs will be crucial for promoting sustainable agricultural practices. Originality/value This review contributes to the existing literature by providing a comprehensive and systematic overview of SFSCs, addressing gaps left by previous review studies. The study's findings offer valuable insights for policymakers, researchers, and stakeholders seeking to enhance the adoption and support of SFSCs in contemporary food systems.